Distinctiveness of annual-ring and its relationship with altitudinal and life zones, and climate type - Moya, Roger; Quesada-Román, Adolfo; Quesada-Monge, Ruperto (Instituto Tecnológico de Costa Rica, 2025)
Costa Rica tiene un clima tropical compuesto por diferentes zonas de vida donde crecen muchas especies arbóreas. Este estudio busca establecer diferentes tipos de distintividad de los anillos anuales (AR) y potencial dendrocronológico (DP) de 320 datos de madera para Costa Rica, un país neotropical. Además, se estableció la relación entre la distintividad y el DP con el tipo de especie, condición de crecimiento, nivel altitudinal, zonas de vida, y tipo de clima. Los resultados indicaron que 70 especies (21.9%) no presentaron límite de AR (con ningún DP), 104 especies (32.5%) presentaron AR bien definido (+) (con alto DP) y las especies restantes (146 especies o 45.6% del total) presentaron AR más o menos distintivo (+/-), luego el DP varió de medio a bajo. Las 8 especies que crecen exclusivamente en condiciones tropicales secas y presentaron una AR bien definida (con un DP alto), pero 137 especies (73,3%) que crecen en condiciones tropicales lluviosas presentaron una AR ausente o poco definida, por lo que el DP varió de medio a bajo. Muchas especies (67) que crecen en zonas bajas y altas (basales y premontanas) presentaron un DP nulo, mientras que muchas especies presentaron un DP positivo (DP medio) y 41 especies mostraron un DP alto. Pocas especies crecen en zonas altas (cordilleras y subalpinas), pero presentaron una AR poco distintiva, por lo que se presentaron DP altos. Finalmente, muchas especies presentan DP medio y alto, por lo que las aplicaciones de la dendrocronología fueron limitadas.

Costa Rica has a tropical climate composed by diverse life zones with large quantity of tree species. This study aims to establish different types of the annual rings (AR) distinctiveness, and dendrochronological potential (DP) of 320 wood data for Costa Rica, a neotropical and central America country. Besides it was established the relation among distinctiveness and DP species type, growing condition, altitudinal level and life zones, and climate type. So, it can serve as a basis for a proposal of tree species with dendrochronological potential in South America and the neotropics region. The results indicated 70 species (21.9%) did not present AR boundary (with any DP), 104 species (32.5%) presented well-defined (+) AR (with high DP) and the remaining species (146 species or 45.6% of the total) presented more or less distinctive (+/-) AR, then DP varied from medium to low. The 8 species that grow exclusively in dry tropical conditions presented well-defined AR (with high DP), but 137 species (73.3%) that grow in rainy tropical condition presented absent or poor defined AR, then DP varied from medium to low. Many species (67) that grow in low high (basal and premontane) presented null DP and many species presented (+/-) (medium DP) and 41 species shown high DP. Few species grow in high part (montane and subalpine), but barely presented distinctive AR, then high DP are presented. Finally, many species present medium and high DP, the applications of dendrochronology were limited.
Artículo (Preimpresión: versión no revisada por pares) Instituto Tecnológico de Costa Rica (ITCR). Escuela de Ingeniería Forestal, Universidad de Costa Rica (UCR). Departamento de Geografía, 2025
Keywords: Especies latifoliadas; Dendroclimatología; Anillo de crecimiento; Dendrogeomorfología; Especies tropicales; Condiciones tropicales secas; Bosques tropicales; Condiciones tropicales lluviosas; Especies arbóreas; Plantaciones forestales; Sistemas agroforestales; Broadleaved species; Dendroclimatology; Growth ring; Dendrogeomorphology; Anillos de los árboles; Tropical species; Tropical dry conditions; Tropical forests; Tropical rainy conditions; Tree species; Forest plantations; Agroforestry systems; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING